2018
DOI: 10.1038/nature26162
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Asparagine bioavailability governs metastasis in a model of breast cancer

Abstract: This corrects the article DOI: 10.1038/nature25465.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Both L-asparagine and putrescine have been implicated in the promotion of cell growth [54][55][56][57][58][59] . Our data indicates cell lines with higher levels of NAT1 activity have increased amounts of N-acetylated asparagine and putrescine while cell lines with decreased and knocked-out NAT1 activity have decreased amounts of N-acetylated asparagine and putrescine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both L-asparagine and putrescine have been implicated in the promotion of cell growth [54][55][56][57][58][59] . Our data indicates cell lines with higher levels of NAT1 activity have increased amounts of N-acetylated asparagine and putrescine while cell lines with decreased and knocked-out NAT1 activity have decreased amounts of N-acetylated asparagine and putrescine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that intracellular asparagine exchanges with extracellular amino acids to promote mTORC1 activation, protein and nucleotide synthesis and cell proliferation under normal growth www.nature.com/scientificreports www.nature.com/scientificreports/ (non-starvation) conditions 55 . Additionally, it has been reported that the invasiveness of a mouse breast cancer model could be modulated either by altering asparagine biosynthetic capacity or by modifying extracellular asparagine pools with decreases in asparagine leading to decreased metastatic burden 54 . Polyamines, such as putrescine, are known to facilitate the interactions of transcription factors, such as estrogen receptors with their specific response element and are involved in the proliferation of ER negative breast cancer tumor cells (reviewed in 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies performed in endothelial cells, Kaposi's sarcoma-associated herpesvirus (KSHV)transformed cancer cells and several normal fibroblast or epithelial cell lines reported a similar effect of asparagine on supporting cell survival and protein translation after glutamine deprivation 44,49,50 . Interestingly, high intracellular asparagine levels have recently been identified to be essential for breast cancer metastasis 51 . This study suggested that L-asparaginase treatment alone can reduce the incidence of breast cancer metastasis to the lung without affecting primary tumor growth.…”
Section: Asparaginementioning
confidence: 99%
“…However, to probe the mechanistic basis of these phenotypes, clonal lineages had to be established by single-cell isolation and used to reconstitute a heterogeneity model from a limited initial diversity. Fortunately, those same phenotypes were observed in a collection of 23 clonal lines, enabling the use of molecular profiling to identify vascular mimicry as a driver of CTC forming potential and asparagine bioavailability as a driver of metastasis through its impacts on EMT [7,8] The need for manual isolation of clonal lineages as an intermediate step toward the study of heterogeneous populations raises a substantial barrier to the exploration of a plurality of models and the synthesis of insights derived from them. As an example, tumour cells vary in their sensitivity to therapeutic agents, ranging from sensitive to tolerant to resistant [9].…”
Section: Introductionmentioning
confidence: 91%